Forecasting fixed assets and their depreciation in conditions of volatile demand for production capabilities - Ciupek, Bożena; Kaczmarzyk, Jan (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
A significant element of managing corporate finance is forecasting the financial situation of an enterprise. Forecasting means drawing up simplified financial statements (pro- -forma). One of the basic components of a financial situation forecast is estimating both: fixed asset levels, as well as their depreciation. In a volatile environment, the natural assumption is volatile demand for production capabilities, as a consequence of volatile economic conditions. Furthermore, eventual changes of the production capabilities being the consequence of purchasing and selling fixed assets are not smooth. Taking the above into account, the authors propose the concept of a financial model for forecasting fixed assets and their depreciation. The implementation of the model is also presented using a case study
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 17-28
Keywords: financial modelling; forecasting; corporate finance; risk; Monte Carlo approach; modelowanie finansowe; prognozowanie; finanse przedsiębiorstwa; ryzyko; metoda Monte Carlo